The Establishment of a Disciplined Character Development Module Through Scouting Extracurriculars - Muktadil Arya Nugraha; Zuwirna Zuwirna; Z. Mawardi Effendi; Azwar Ananda (Jurnal Penelitian Pendidikan IPA, 2023)
The expected goal of this development research is to describe the process of developing a discipline character-building module through scout extracurriculars in high school, and to find out the validity, practicality, and effectiveness of developing a discipline character-building module through scout extracurriculars in high school. This type of research is Research and Development (R&D) research, with the ADDIE model which consists of five stages, namely the analysis stage (analysis), the planning stage (design), the development stage (development), the implementation stage (implementation), and the evaluation stage (evaluation). Meanwhile, the subject studied was the development of a discipline character-building module through extracurriculars at Murni Padang High School, while the subject being developed was a discipline character-building module in scout extracurriculars. The results of this research show that the module developed is declared valid with a validation assessment score for the module material of 4.64 and is classified as very good; validation of the module form was 4.45 with a very good classification, while the response questionnaire from the coaching instructor obtained a score of 4.55 and was classified as very good so that it was suitable for use in developing disciplined character through scout extracurriculars and the results of the coaching results test carried out at the end of the research, the module developed was categorized as effective. This is shown by the percentage of learning completion for coaching participants which is in a very good classification with an average result of 28 participants (95.63%) of respondents being declared complete (passed) and only 2 participants (4.37%) of respondents who have not completed (did not pass).